1985
DOI: 10.1111/j.1399-6576.1985.tb02220.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adjuvants to Local Anaesthetics on Their Duration

Abstract: The effects of addition of hyaluronic acid (sodium hyaluronate, Healon) to different local anaesthetics of the amide type on the duration of sensory or motor blocks following various regional anaesthetic procedures were studied in animal experiments. In the rat infra-orbital nerve block model, the addition of 0.1-0.5% hyaluronic acid (HA) to 2% prilocaine increased the duration of sensory block of varying degrees in a dose-dependent way by up to 500% of values obtained with plain prilocaine. The duration of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…These findings suggest that hyaluronan, if mixed with bupivacaine, may not affect bupivacaine's anesthetic function. It has been reported in animal [17] and human studies [18] that the duration of sensory nerve blockade from bupivacaine is prolonged by addition of hyaluronan. Hassan et al described this extended action of the local anesthetic, but they did not determine the exact mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that hyaluronan, if mixed with bupivacaine, may not affect bupivacaine's anesthetic function. It has been reported in animal [17] and human studies [18] that the duration of sensory nerve blockade from bupivacaine is prolonged by addition of hyaluronan. Hassan et al described this extended action of the local anesthetic, but they did not determine the exact mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Hassan et al described this extended action of the local anesthetic, but they did not determine the exact mechanism. They speculated that hyaluronan may bind to the local anesthetic drug, thereby delaying the drug's access to the channel proteins [17]. We have previously shown that hyaluronan can prevent bupivacaine-induced chondrotoxicity [11].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the benefits typically achieved by increasing the polymer concentration (and thus the viscosity) of the delivery vehicle are minimized because of the rapid rate of HA hydration. Indeed, this hydration phenomenon may contribute to the inconsistencies in the literature regarding the effectiveness of viscous HA solutions as a delivery vehicle for local anesthetics 15, 20, 21. Blending a lower humectancy polymer such as HPMC reduces the rate of bulk polymer hydration, thereby maintaining a coherent, high‐viscosity gel delivery vehicle for a longer period of time in vivo and facilitating more prolonged bupivacaine release.…”
Section: Discussionmentioning
confidence: 99%
“…The successful use of polymer solutions (or blends) in drug delivery therefore depends directly on the biophysical properties of the chosen polymers. Hyaluronic acid (HA), a linear polysaccharide composed of alternating units of β‐1,4‐ D ‐glucuronic acid and β‐1,3‐ N ‐acetyl‐ D ‐glucosamine, is of particular interest because of its good biocompatibility, excellent humectancy, and high aqueous solubility; its anionic charge may also be useful to improve the retention of cationic local anesthetics within the matrix 15–22. However, viscoelastic solutions have been inconsistent in prolonging the duration of nerve blockade in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to slow the drug-release process and prolong drug action, different strategies have been adopted, either by modulating the interaction between the drug and hydrogel matrix or by modifying the gel network. Taking advantage of interactions between ionic polymers and charged loading agents, drugs such as naphazoline [31], NSAIDs [32], anesthetics [33], and amphotericin B [34] have been successfully conjugated to different kinds of hydrogel system for sustained drug release. Drugs can also be covalently linked to polymers, but the release process is initiated by chemical or enzymatic cleavage of the polymer–drug linkage.…”
Section: Aptamer-incorporated Hydrogel For Controlled Drug Release Anmentioning
confidence: 99%